2007
DOI: 10.1080/13658810701349011
|View full text |Cite
|
Sign up to set email alerts
|

Geovisual analytics for spatial decision support: Setting the research agenda

Abstract: This article summarizes the results of the workshop on Visualization, Analytics & Spatial Decision Support, which took place at the GIScience conference in September 2006. The discussions at the workshop and analysis of the state of the art have revealed a need in concerted cross-disciplinary efforts to achieve substantial progress in supporting space-related decision making. The size and complexity of real-life problems together with their ill-defined nature call for a true synergy between the power of comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
224
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(229 citation statements)
references
References 18 publications
1
224
0
4
Order By: Relevance
“…In contrast, Kraak (2008) suggested that "geovisualisation" was seeing inflation as a term: namely, that geovisualisation was being used increasingly widely and indiscriminately, becoming equated with "mapping", and therefore increasingly less useful as a term. So, he favours the use of the term "geovisual analytics" (Thomas & Cook, 2005;Andrienko et al 2007) for the range of activities in and around the geovisualisation cube, implicitly retaining a more focused definition of "geovisualisation". Discussion exists about the terminology surrounding geographic visualisation, yet, at its simplest, geovisualisation is simply a synthesis of the long-developed visual communication of cartography with current digital analytical technologies, principally GIS.…”
Section: Geomorphology and Geovisualisationmentioning
confidence: 99%
“…In contrast, Kraak (2008) suggested that "geovisualisation" was seeing inflation as a term: namely, that geovisualisation was being used increasingly widely and indiscriminately, becoming equated with "mapping", and therefore increasingly less useful as a term. So, he favours the use of the term "geovisual analytics" (Thomas & Cook, 2005;Andrienko et al 2007) for the range of activities in and around the geovisualisation cube, implicitly retaining a more focused definition of "geovisualisation". Discussion exists about the terminology surrounding geographic visualisation, yet, at its simplest, geovisualisation is simply a synthesis of the long-developed visual communication of cartography with current digital analytical technologies, principally GIS.…”
Section: Geomorphology and Geovisualisationmentioning
confidence: 99%
“…13 This is increasing opportunities for (geo)visual analysis 14 and is fuelling the emerging field of visual analytics. 8,15 In this context, visual data exploration techniques can be used to identify patterns of interest that may relate to significant characteristics of the phenomenon under study. Importantly, they may also help draw attention to biases and data quality issues in large informal data sets of unknown quality.…”
Section: Datamentioning
confidence: 99%
“…Data-mining techniques can help reduce this search space by selecting subsets worthy of further comparison and their combination with visualisation techniques is characteristic of visual analytics. 8 We have developed a novel visual approach that uses treemaps with spatial and temporal ordering to simultaneously present thousands of summaries of variable-constrained subsets of a 42.2 million record data set. These serve as rich data-dense overviews whose systematically ordered nature may facilitate the broad comparison of subsets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has focused on geovisualization (MacEachren & Kraak, 1997;MacEachren, 1994;Virrantaus, Fairbairn, & Kraak, 2009), geovisual analytics (Andrienko et al, 2007), representational techniques (Skupin & Fabrikant, 2003) and interaction paradigms (Peterson, 1997;Roth, 2013), among others too numerous to fully explore here. A key motivation for the articles presented here was to complement seminal work in a special issue of Cartography and Geographic Information Science, published in 2001, which resulted in a range of new research agendas for cartography that spanned the most urgent topics of that time, some of which persist today (MacEachren & Kraak, 2001;Cartwright et al, 2001;Fairbairn, Andrienko, Andrienko, Buziek, & Dykes, 2001;Gahegan, Wachowicz, Harrower, & Rhyne, 2001;Slocum et al, 2001).…”
Section: Introductionmentioning
confidence: 99%